The Aeronian/Telychian (Llandovery, Silurian) boundary, with particular reference to sections around the El Pintado reservoir, Seville Province, Spain - Loydell, D. K.; Frýda, Jiri; Gutiérrez-Marco, J. C. (Bulletin of Geosciences, 2015)
The upper Aeronian to lower Telychian (Llandovery Series, lower Silurian) strata at the east end of El Pintado reservoir, Seville Province, Spain are documented in terms of their lithologies, graptolite biostratigraphy and δ13Corg record. This is the first time that a continuously graptolitic section throught the Aeronian/Telychian boundary has been studied in detail. The upper Aeronian part of the section is assigned to the Stimulograptus halli Biozone which is divisible into three, the middle part being referred to the Lituigraptus rastrum Subzone. The Telychian strata are assigned to the Spirograptus guerichi Biozone and lower Sp. turriculatus Biozone. Unusually, two specimens of Sp. turriculatus were found at a level low in the guerichi Biozone. 118 graptolite species are recorded, 18 of which are new and described here together with other species for which the El Pintado material provides new information. Diversity increases considerably in some genera (Glyptograptus, Parapetalolithus, Rastrites, Streptograptus) in the upper halli Biozone and/or lower to middle guerichi Biozone only to decline again (except for Streptograptus) in the upper part of the guerichi Biozone as part of the “utilis Event”. This diversity decline coincides with an interval of elevated δ13Corg values. There are no major δ13Corg excursions present in the El Pintado sections. The δ13Corg record through the guerichi Biozone is very similar to that in Arctic Canada. • Key words: graptolite, biostratigraphy, palaeobiogeography, Aeronian, Telychian, Llandovery, Spain. The research was supported by the Grant Agency of the Czech Republic (GAČR 15-13310S), and a grant from the Czech Geological Survey (338800). This paper is a contribution to IGCP Project 591, the Early to Middle Paleozoic Revolution. Peer reviewed